Late manifestation of follicular conjunctivitis in ventilated patient following COVID-19 positive severe pneumonia - Bhagabat Nayak; Chanchal Poddar; Manoj Kumar Panigrahi; Swagata Tripathy; Baijayantimala Mishra (Indian Journal of Ophthalmology, 2020)
A 65-year-old known diabetic, hypertensive, and asthmatic patient was admitted for suspected coronavirus disease 19 (COVID-19) infection following complaints of breathlessness. He tested positive for COVID-19 and was put on ventilation. He developed severe follicular conjunctivitis of the right eye while on a ventilator, which was treated conservatively. The resolution of ocular signs was noted over 2 weeks without any complications. This case highlights the timeline of events and discusses the late ophthalmic manifestations in patients with COVID-19 infection.